The Implicit Association of High-Fat Food and Shame Among Women Recovered From Eating Disorders - Elran-Barak, Roni; Dror, Tzipi; Goldschmidt, Andrea B.; Teachman, Bethany A. (Frontiers in Psychology, 2020)
Background: Despite the growing literature about recovery from eating disorders (EDs), it is still unknown if women who report being recovered from EDs present with differing implicit attitudes about high-fat (vs. low-fat) food relative to women who report having a current ED and women who report never having an ED. Methods: Female volunteers (N = 2,785) to the project implicit mental-health website (https://implicit.harvard.edu/) were divided into three ED groups: current ED (n = 335), prior ED (n = 393), and healthy controls (n = 1,843). Participants completed, between 2016 and 2017, a background questionnaire, together with the Implicit Association Test (IAT), measuring implicit associations between high-fat (vs. low-fat) food and shame (vs. acceptable). Linear regression models were conducted to examine cross-sectional differences between groups. Results: Women with prior EDs had stronger implicit associations relative to healthy controls (p = .041), and similar implicit associations relative to women with current EDs (p = .424). Discussion: The implicit association between high-fat food and shame may not diminish over time among women with EDs. Future longitudinal studies are warranted to clarify whether an experience of EDs may leave a “scar”, manifested in specific implicit associations, that may potentially lead to recurrence after remission.